2018
DOI: 10.1111/pan.13423
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between minute carbon dioxide elimination and pulmonary blood flow in single‐ventricle patients after stage 1 palliation and 2‐ventricle patients with intracardiac shunts: A pilot study

Abstract: Volume of CO elimination may be a surrogate marker of pulmonary blood flow in single-ventricle patients and patients with biventricular physiology with intracardiac shunting. Also, among patients with normal cardiac anatomy, volume of CO elimination may be a marker of cardiac output.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…In contrast, poor correlation between cardiac output and VCO 2 is seen in patients with single ventricle physiology and significant intracardiac shunts. 11 In our series, VCO 2 remained similar to predecannulation levels or improved suggesting adequacy of Q p (and hence cardiac output). VCO 2 did trend lower in the two nonsurvivors as well as in the patient with dilated cardiomyopathy where ECMO was used as a bridge to LVAD placement, suggesting poor cardiac output/Q p .…”
Section: Discussionsupporting
confidence: 64%
“…In contrast, poor correlation between cardiac output and VCO 2 is seen in patients with single ventricle physiology and significant intracardiac shunts. 11 In our series, VCO 2 remained similar to predecannulation levels or improved suggesting adequacy of Q p (and hence cardiac output). VCO 2 did trend lower in the two nonsurvivors as well as in the patient with dilated cardiomyopathy where ECMO was used as a bridge to LVAD placement, suggesting poor cardiac output/Q p .…”
Section: Discussionsupporting
confidence: 64%
“…Alteration of minute ventilation causes EtCO 2 and VCO 2 to move in opposite directions, while changes in PBF, and by extension CO, move EtCO 2 and VCO 2 in the same direction. 25 Therefore, the use of both VCO 2 and EtCO 2 during resuscitation might ensure that changes in EtCO 2 are secondary to changes in the quality of chest compression rather than changes in minute ventilation. Berg et al 26 showed that in asphyxia cardiac arrest that EtCO 2 was initially elevated during the first few breaths of CPR and rapidly dropped.…”
Section: Discussionmentioning
confidence: 99%